2009
DOI: 10.1007/s11205-009-9494-x
|View full text |Cite
|
Sign up to set email alerts
|

Happy to Help? Exploring the Factors Associated with Variations in Rates of Volunteering Across Europe

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThe frequency of formal volunteering varies widely across European countries, and rates of formal volunteering are especially low among Eastern European countries. Why are there such large differences in volunteering rates when it is known that volunteering is beneficial for well-being? Using data from the latest round of the European Social Survey, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 39 publications
(53 reference statements)
8
99
1
2
Order By: Relevance
“…In the last twenty years, numerous studies in developed countries have shown parents reporting significantly lower or not significantly different well-being compared to non-parents with the number of children negatively affecting the most diverse subjective well-being measures (Clark and Oswald, 2002;Di Tella et al, 2003;Dockery, 2010;Hansen, 2012;Peiró, 2006;Plagnol and Huppert, 2010). Nevertheless, the link between these two variables appears mitigated or even reversed by the effect of other factors: parity, gender, marital status, economic status, welfare state.…”
Section: Subjective Well-being and Fertilitymentioning
confidence: 99%
“…In the last twenty years, numerous studies in developed countries have shown parents reporting significantly lower or not significantly different well-being compared to non-parents with the number of children negatively affecting the most diverse subjective well-being measures (Clark and Oswald, 2002;Di Tella et al, 2003;Dockery, 2010;Hansen, 2012;Peiró, 2006;Plagnol and Huppert, 2010). Nevertheless, the link between these two variables appears mitigated or even reversed by the effect of other factors: parity, gender, marital status, economic status, welfare state.…”
Section: Subjective Well-being and Fertilitymentioning
confidence: 99%
“…Några tidigare studier, som använt material från olika databaser (t.ex. SHARE, European Social Survey eller Eurobarometer) med en vid definition av anhörigomsorg, har visat att anhörigas insatser till någon man inte bor tillsammans med är omfattande i de skandinaviska länderna i jämförelse med länder i södra Europa (van Campen, de Boer & Ledema, 2013;Hank & Stuck, 2008, OECD, 2011Oudijk, Woittiez & de Boer, 2011;Plagnol & Huppert, 2009). De flesta av dessa studier visar dock inte hur mycket hjälp som ges eller hur lång tid åtagandet pågår.…”
Section: Civilsamhället Som Arena För Omsorgunclassified
“…In the same way, it should be noted how periods of economic crisis have not left much time for people to volunteer. Then, in an economic recession context, CV has tended to be seen as superfluous, dispensable, and away from the core business (Plagnol and Huppert, 2010). Leaving aside these more macroeconomic variables, literature show that time is the main barrier to employee involves in CV (Geroy, et al, 2000).…”
Section: Motivations Arising From Job Satisfaction Autonomy and Selfmentioning
confidence: 99%